Krameria lappacea root extract’s anticoccidial properties and coordinated control of CD4 T cells for IL-10 production and antioxidant monitoring - Abdel-Gaber, Rewaida; Alamari, Ghada; Dkhil, Mohamed A.; Meryk, Andreas; Al-Shaebi, Esam M.; Al-Quraishy, Saleh (Frontiers in Immunology, 2024)
Recently, the use of botanicals as an alternative to coccidiostats has been an appealing approach for controlling coccidiosis. Therefore, this study was conducted to evaluate the potential role of aqueous methanolic extract (200 mg/kg) of Krameria lappacea (roots) (KLRE) against infection induced by Eimeria papillata. A total of 25 male C57BL/6 mice were divided into five groups (I, II, III, IV, and V). On 1st day of the experiment, all groups except groups I (control) and II (non-infected-treated group with KLRE), were inoculated orally with 103 sporulated E. papillata oocysts. On the day of infection, group IV was treated with KLRE. Group V served as an infected-treated group and was treated with amprolium (coccidiostat). Treatment with extract and coccidiostat was continued for five consecutive days. While not reaching the efficacy level of the reference drug (amprolium), KLRE exhibited notable anticoccidial activity as assessed by key criteria, including oocyst suppression rate, total parasitic stages, and maintenance of nutrient homeostasis. The presence of phenolic and flavonoid compounds in KLRE is thought to be responsible for its positive effects. The Eimeria infection increased the oxidative damage in the jejunum. KLRE treatment significantly increased the activity of catalase and superoxide dismutase. On the contrary, KLRE decreased the level of malondialdehyde and nitric oxide. Moreover, KLRE treatment decreased macrophage infiltration in the mice jejunal tissue, as well as the extent of CD4 T cells and NFkB. E. papillata caused a state of systemic inflammatory response as revealed by the upregulation of inducible nitric oxide synthase (iNOs)-mRNA. Upon treatment with KLRE, the activity of iNOs was reduced from 3.63 to 1.46 fold. Moreover, KLRE was able to downregulate the expression of pro-inflammatory cytokines interferon-𝛾, nuclear factor kappa B, and interleukin-10 -mRNA by 1.63, 1.64, and 1.38 fold, respectively. Moreover, KLRE showed a significant reduction in the expression of IL-10 protein level from 104.27 ± 8.41 pg/ml to 62.18 ± 3.63 pg/ml. Collectively, K. lappacea is a promising herbal medicine that could ameliorate the oxidative stress and inflammation of jejunum, induced by E. papillata infection in mice.